Polymer Spot Size Expanders for High Efficiency Optical Coupling in Optical Interconnection - Kamiura, Yoshiki; Kurisawa, Taiga; Fujikawa, Chiemi; Mikami, Osamu (Photonics Letters of Poland, 2022)
Improving the low coupling efficiency due to spot size differences between silicon photonics chips and single mode fibers remains a challenge for achieving high bit-rate optical interconnections. To solve this problem, the test spot size expander device is fabricated using UV-curable resin on the end face of a fiber with a high numerical aperture having a similar spot size of silicon chips. The expanded spot size of 9.38 μm from the original 3.2 μm at a wavelength of 1.55 μm and the maximum coupling efficiency with a single mode fiber of –1.19 dB is achieved. In addition, the –3 dB tolerance of the coupling efficiency along the vertical optical axis was ±4.1 µm. Full Text: PDF References R. Marchetti, C. Lacava, L. Carroll, K. Gradkowski, P. Minzioni, "Coupling strategies for silicon photonics integrated chips", Photonics Res. 7, 201 (2019). CrossRef R. Bachelot, C. Ecoffet, D. Deloeil, P. Royer, D.J. Lougnot, "Integration of micrometer-sized polymer elements at the end of optical fibers by free-radical photopolymerization", Appl. Opt. 40, 5860 (2001). CrossRef L. Xiao, W. Jin, M. S. Demokan, H. L. Ho, H. Y. Tam, J. Ju, J. Yu, "Photopolymer microtips for efficient light coupling between single-mode fibers and photonic crystal fibers", Opt. Lett. 31, 1791 (2006). CrossRef O. Mikami, R. Sato, S. Suzuki, C. Fujikawa, "Polymer Microlens on Pillar Grown From Single-Mode Fiber Core for Silicon Photonics", IEEE Photonics Technol. Lett. 32, 399 (2020). CrossRef Y. Kamiura, T. Kurisawa, C. Fujikawa, O. Mikami, "High optical coupling efficiency of polymer microlens and pillar on single mode fiber for silicon photonics", Jpn. J. Appl. Phys. 61 SK1009, (2022). CrossRef T. Kurisawa, Y. Kamiura, C. Fujikawa, O. Mikami, "Application of a Polymer Microlens with a Pillar for High Efficiency Coupling between Single Mode Fibers and SiPh Chips", Proc. 2021 IEEE CPMT Symposium Japan (ICSJ), 102 (2021). CrossRef H. Terasawa and O. Sugihara, "Near-Infrared Self-Written Optical Waveguides for Fiber-to-Chip Self-Coupling", J. Lightwave Technol., 39, 7472 (2021) CrossRef Y. Saito, K. Shikama, T. Tsuchizawa, N. Sato, "Tapered self-written waveguide for a silicon photonic chip I/O", Opt. Lett., 47, 2971 (2022). CrossRef A. Noriki, I. Tamai, Y. Ibusuki, A. Ukita, S. Suda, D. Shimura, Y. Onawa, H. Yaegashi, T. Amano, "Mirror-Based Broadband Silicon-Photonics Vertical I/O With Coupling Efficiency Enhancement for Standard Single-Mode Fiber", J. Lightwave Tech. 38, 3147 (2020). CrossRef T. Amano, A. Noriki, I. Tamai, Y. Ibusuki, A. Ukita, S. Suda, T. Kurosu, K. Takemura, T. Aoki, D. Shimura, Y. Onawa, H. Yaegashi, "Polymer Waveguide-coupled Co-packaged Silicon Photonics-die Embedded Package Substrate", OFC2021, Th4A.1, (2021). CrossRef S. J. Frisken, "Light-induced optical waveguide uptapers ", Opt. Lett. 18, 1035 (1993). CrossRef Y. Obata, Y. Oyama, H. Ozawa, T. Ito, O. Mikami, T. Uchida, "Multi-array Self-Written Waveguides using Photo-mask for Optical-Surface Mount Technology", ICEP2005, 225 (2005). DirectLink Y. Kamiura, T. Kurisawa, C. Fujikawa, O. Mikami, "Application of a Polymer Microlens with a Pillar for High Efficiency Coupling between Single Mode Fibers and SiPh Chips", Proc. 2021 IEEE CPMT Symposium Japan (ICSJ), 104 (2021). CrossRef N. A. Baharudin, C. Fujikawa, O. Mikami, S. M. Idrus, S. Ambran, "UV-curable resin microlenses on optical pillars for optical interconnect", Jpn. J. Appl. Phys. 58, SJJB02, (2019). CrossRef K. Kawano, "Coupling characteristics of lens systems for laser diode modules using single-mode fiber", Appl. Opt. 25, 2600 (1986). CrossRef H. Nawata, K. Ohmori, "Organic-Inorganic Hybrid Material for Optical Interconnects and Application to Optical Coupling Method", Proc. International Conference on Electronics Packaging (ICEP), Toyama, Japan, Apr. 23-25, (2014). CrossRef P. Yin, J.R. Serafini, Z. Su, R-J. Shiue, E. Timurdogan, M.L. Fanto, S. Preble, "Low connector-to-connector loss through silicon photonic chips using ultra-low loss splicing of SMF-28 to high numerical aperture fibers", Opt. Express 27, 24188 (2019). CrossRef https://coherentinc.force.com/Coherent/UHNA7?cclcl=en_US, DirectLink